The Effect of Quality of Work Life and Organizational Commitment toward Employee's Performance - Yohaningsih, Yohaningsih; Gozali, Imam (Untag Business and Accounting Review, 2022)
This study aims to determine the effect of the quality of work life and organizational commitment on employee performance of BPJS Ketenagakerjaan in Semarang. The population used in this study was all employees at BPJS Ketenagakerjaan in Semarang. The sample size was 90 respondents, taken with a simple random sampling technic. The data source used is primary data, with the data collection method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results indicate that the quality of work life has a positive and significant effect on employee performance, and organizational commitment has a positive and significant effect on employee performance. Based on the results, suggestions can be submitted to BPJS Employment Semarang to maintain or improve work life and organizational commitment, by providing rewards and compensation for excellent employees.